2017
DOI: 10.1002/jcp.25751
|View full text |Cite
|
Sign up to set email alerts
|

Super‐resolution structure of DNA significantly differs in buccal cells of controls and Alzheimer's patients

Abstract: The advent of super‐resolution microscopy allowed for new insights into cellular and physiological processes of normal and diseased cells. In this study, we report for the first time on the super‐resolved DNA structure of buccal cells from patients with Alzheimer's disease (AD) versus age‐ and gender‐matched healthy, non‐caregiver controls. In this super‐resolution study cohort of 74 participants, buccal cells were collected and their spatial DNA organization in the nucleus examined by 3D Structured Illuminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The automated assay used in these studies, which was developed using laser scanning cytometry, also demonstrated higher levels of Aβ in AD compared to control cells [ 162 ]. More recent findings by other groups of telomere changes [ 159 ] and DNA structural changes [ 163 ] in buccal cells in AD compared to controls add to the evidence that AD is a systemic pathology. The evidence also supports the potential of an AD combined peripheral biomarker panel, which would aid in early diagnosis and the testing and monitoring of potential therapies.…”
Section: Other Diagnostic Avenuesmentioning
confidence: 89%
“…The automated assay used in these studies, which was developed using laser scanning cytometry, also demonstrated higher levels of Aβ in AD compared to control cells [ 162 ]. More recent findings by other groups of telomere changes [ 159 ] and DNA structural changes [ 163 ] in buccal cells in AD compared to controls add to the evidence that AD is a systemic pathology. The evidence also supports the potential of an AD combined peripheral biomarker panel, which would aid in early diagnosis and the testing and monitoring of potential therapies.…”
Section: Other Diagnostic Avenuesmentioning
confidence: 89%
“…Apart from helping solve basic problems, SRM is applied in the study of processes that occur in cell nuclei in various pathologies. SRM has been used to study Hutchinson-Gilford progeria [150], Alzheimer’s disease [151], hypoxia and fasting in cardiomyocytes, oncogenesis [21, 152], and viral infections [150, 151]. SRM-based techniques have been developed for the diagnosis of diseases, in particular cancers [153].…”
Section: Resultsmentioning
confidence: 99%
“…The three-dimensional nanometer-scale resolution enabled by 3D SIM has transformed our understanding of DNA structure, allowing visualization of chromatin distribution within the cell nucleus inaccessible to conventional light optical techniques [18][19][20][21][22]. Super-resolution (SR) imaging has evolved from a tool built and used by physicists, to a commercially available imaging system that is now more broadly applied to multiple fields, especially in the past decade when it became obvious that sub-Abbe resolution of cellular structures became feasible and enhanced our knowledge of structures in cells dramatically [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of nuclear chromatin distribution has been proven to be a highly effective tool to quantify changes in chromatin architecture associated with malignancy and disease progression [20][21][22]. The value of super-resolution microscopy technique in assessing and quantifying differences in nuclear structure between normal and disease cells has already been demonstrated in Hodgkin's lymphoma, multiple myeloma and in Alzheimer's disease [12,[18][19][21][22]. The first comprehensive 3D SIM studies investigating the 3D nuclear DNA organization in cancer and addressing the changes in the organization were performed by our group [12,16,17].…”
Section: Discussionmentioning
confidence: 99%